Correlation Analysis of the Bacterial Community and Wood Properties of Populus × euramericana cv. “74/76” Wet Heartwood - Fan, Jianmin; Wang, Shijie; Ding, Changjun; Ma, Changming; Chen, Xinghao; Wang, Jinmao; Yang, Minsheng; Su, Xiaohua (Frontiers in Microbiology, 2022)
Wetwood disease of poplar limits the processing and manufacturing of poplar and the pathogenic bacteria of wet heartwood are poorly understood. We used high-throughput sequencing methods to analyze the bacteria of the heartwood, sapwood, root tissue, and rhizosphere soil of Populus × euramericana cv. ‘74/76’ (poplar 107) wetwood trees and normal trees to explore the reasons for poplar wetwood disease. Diversity and community structure were analyzed, and the correlation between wood properties and microbes was analyzed to explore the relationship between the microbial communities and the wood properties. The diversity index of endophytic bacteria in the heartwood of wetwood trees was significantly (p < 0.05) lower than that in the heartwood of normal trees, and the community structure between the two types of trees was significantly different. No significant differences in the alpha diversity index or community structure were observed between the sapwood, root tissue, and rhizosphere bacteria of the two types of trees. Proteiniphilum, Sporobacter, Methanomassiliicoccus, Anaerocolumna, Christensenellaceae_R-7_group, and Dysgonomonas were the dominant genera in the heartwood samples. The relative abundances of Proteiniphilum, Actinotalea, and Methanobacterium were significantly higher in the heartwood of wetwood trees than those of normal trees, and were positively correlated with the rate of wet heartwood. These three bacteria may be the main pathogens causing poplar wetwood disease.